2019
DOI: 10.1002/mawe.201800119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process variables on the characteristics of friction‐stir‐welded polyamide 6,6 joints

Abstract: This paper aims to study the feasibility of friction stir welding of thermoplastic material polyamide 6,6. The maximum joint strength achieved through the optimized process variables is 41 MPa. The maximum temperature rise of 126 °C is achieved and the weld nugget exhibits a hardness of 69 D on Shore hardness scale. Fractography analysis reveals that the fracture followed a continuous plastic flow comprising less prominent fibrillation and more elongated voids. An increase in glass transition temperature Tg is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The subsequent cooling rate was also slow. The heat was concentrated around the tool and heat flux on top surface of base materials was limited [65]. These observations confirmed that the temperature distribution during LFSW of polymers is much different as compared to that observed in metals.…”
Section: Process Monitoringsupporting
confidence: 64%
“…The subsequent cooling rate was also slow. The heat was concentrated around the tool and heat flux on top surface of base materials was limited [65]. These observations confirmed that the temperature distribution during LFSW of polymers is much different as compared to that observed in metals.…”
Section: Process Monitoringsupporting
confidence: 64%
“…Polyamide polymers are widely used in many aspects of modern life such as mechanical, electrical, and sanitary engineering [ 1 ], in the automotive [ 2 ] and construction industries, and in medical technology, e.g., for artificial joints [ 3 ], surgical instruments, and as suture material [ 1 ]. Additionally, polyamide 6 (PA6) is used for food and medical packaging [ 4 ] and for composite materials [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The suitable revolution pitch values are in the order PVC < HDPE < PA6, and the maximum joint strength efficiency was achieved for HDPE (70%), followed by PVC (45%) and PA6 (35%). Few of the studies have used other pin profile tools like frustum pin [112], tapered cylindrical pin [113], threaded conical pin [114], and milling tool with grooves [115].…”
Section: Butt-joint Configurationmentioning
confidence: 99%
“…The ANOVA results of all the studies are summarized in Table 8. Several thermoplastic materials have been investigated for butt-joint FSW, which include HDPE [1], Nylon-66 [99], glass-filled Nylon 6 (30 wt.%) [104], HMWPE (Teflon stationary shoulder tool with threaded pin) [168], polyamide-6,6 (tapered cylindrical pin) [113], and ABS (3D-printed, wooden stationary shoulder) [43]. All these studies have suggested that rotational speed is the first and traverse speed is the second most influential parameters that affect joint strength.…”
Section: Statistical-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation